THE EFFECT OF GIVING ONLINE DISCUSSION ON STUDENT LEARNING OUTCOMES IN IMPULS AND MOMENTUM MATERIALS - Azzizurrachman, Achmad; Maharta, Nengah; Suana, Wayan (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2020)
AbstractThis study aims to determine the effect of online discussion on student learning outcomes on Impulse and Momentum material. The population in this study were all XI classes of SMA Negeri 15 Bandarlampung who were taking the even semester in the 2017/2018 school year. The method used in this research is Quasi Experimental with the research design of The Nonequivalent Control Group Design, in which one group of subjects is given a certain treatment (experiment), while another group is used as a control class group. The data from the results of this study are quantitative, consisting of the pretest and posttest scores carried out at the beginning and end of the learning process carried out. Based on the research results, there is an effect of providing online discussions on student learning outcomes on Impulse and Momentum material. This is indicated by the N-gain average value of learning outcomes in the experimental class of 0.67, while the average N-gain of learning outcomes in the control class is 0.43. The difference in the average learning outcomes in the experimental class and the control class can be seen from the learning process in each class. In the experimental class, the teacher provides Impulse and Momentum material learning by using an online assignment system outside face-to-face hours at school. Discussions conducted by students before face-to-face learning will make students have a better picture of what material will be studied at the next meeting. This makes students more ready to receive learning material and can understand concepts faster. This is because students have discussed with their friends the problems related to the material during online discussions. On the other hand, not all students in the control class learn the material that the teacher will deliver at the next meeting, so students do not have sufficient initial knowledge. Students who are given online discussion assignments after learning also benefit, they will be reminded again about the material that has been taught in class so that the concepts that have been obtained are increasingly embedded in students. Keywords: Online Discussion, Learning Outcomes, Impulse and Momentum, WhatsAppDOI: http://dx.doi.org/10.23960/jpvti.v2.i2.202003